Winter storms drive offshore transport and modulate phytoplankton blooms in Northern Taiwan, China - Liu, Tao; Shi, Yong; Xu, Xiaomei; Liu, Shengjing; Lyu, Jixuan; Zhang, Shuo; Yang, Guang; Ren, Chunyu; Sheng, Hui; Gao, Jianhua (Journal of hydrology (Amsterdam), 2023)
The East China Shelf Sea (ECSS) is subject to high-frequency storms during winter and spring, with these storm processes serving as a significant driving factor for initiating the outward diffusion of materials from the inner shelf. Inner shelf waters tend to be rich in nutrients, thus their horizontal diffusion is crucial to the marine primary productivity of the outer shelf. However, our understanding of the processes that govern the offshore water mass transport under winter storm oscillations and the mechanisms driving their impact on phytoplankton is currently limited. In this study, we used satellite and reanalysis data from 2003 to 2020 to investigate the modulation mechanism of winter offshore currents (WOC) on phytoplankton bloom (PB) stimulated by storms in Northern Taiwan (NTW). The results revealed that at synoptic scales, winter storms result in higher sea surface height (SSH) and potential energy on the inner side of the front. However, during periods of weakened storms (for example, during north wind relaxation or a shift to southerly winds), a strong WOC is produced in the top 30–50 m of the ocean due to continuous SSH adjustments caused by changed pressure gradients and induced by topography. PB occurs in the offshore waters of the front, driven by a continuous nutrient supply and an increase in photosynthetically available radiation (PAR). On an interannual scale, offshore transport is controlled by the storm's duration and the extent of its weakening. As the climate warms and winter winds in NTW have consistently weakened over the past 20 years, lower turbulent kinetic energy (TKE) and a shallower mixed layer depth (MLD) will promote phytoplankton growth. The results suggest that water level fluctuations caused by high-frequency changes in winter storms are strongly linked to the offshore sediment transport from near-shore waters, impacting the material transport and the health of the ecosystem on the continental shelf.